DECODING CYBERPSYCHOLOGY: KEY TRENDS IN DIGITAL LEARNING - A BIBLIOMETRIC INSIGHT - Herdianto, Roni; Setiawan, Mohamad Arief; Hariyanto, Febri Dwi (Graduate School of Universitas Negeri Malang, 2024)
This bibliometric study aims to analyze the research literature on Cyberpsychology in learning. Cyberpsychology refers to the study of the impact of technology on human behavior, including learning. A bibliometric analysis of scientific documents published in journals indexed in Scopus was performed. The study aimed to identify research trends and collaborations between researchers and locate journals and articles of interest in the thematic area. The study's results will provide insights into the current state of research on Cyberpsychology in learning and identify potential areas for future research.